A prospective study of switching asthma patients from a Fixed-Dose Combination (FDC) Inhaled Corticosteroid [ICS]/Long-Acting Beta Agonist [LABA] therapy delivered by Dry Powder Inhaler (DPI) to ICS/LABA delivered by pressurised Metered Dose Inhaler (pMDI). (April 2022) - Al-Ahmad, Mona; Webb, David
Abstract: Background: Previous real-world studies have suggested that in comparison to a dry powder inhaler (DPI), the rate of critical errors is lower with a pressurised metered dose inhaler (pMDI), and inhaled corticosteroid/long-acting bronchodilator (ICS/LABA) delivered by pMDI is more likely to achieve asthma control. Objectives: To evaluate the acceptability, efficacy, safety and cost-effectiveness of switching asthma patients from an ICS/LABA DPI to an ICS/LABA pMDI in a real-world population in Kuwait. Methods: This was a 12-month, observational, nonblinded, prospective, real world study. Patients with asthma for ≥1 year with 2 or more asthma exacerbations in the last year were assigned to either switch to ICS/LABA pMDI, or to continue with ICS/LABA DPI. Results: A total of 239 patients were treated with either ICS/LABA pMDI (Switch cohort; n = 119) or ICS/LABA DPI (Maintenance cohort; n = 120). The majority of patients (99/119; 83.2%) in the Switch cohort remained on ICS/LABA pMDI over 12 months of follow-up. Both cohorts experienced an improvement in their FEV1 levels, with mean values in the Switch group reaching normal levels (>80% predicted). On average, at 3 and 12 months, the Switch cohort had significantly better FEV1 values than patients in the Maintenance cohort (p = 0.001). At 12 months, the proportion of patients with controlled asthma increased in the Switch group, but did not change significantly in the Maintenance group. Conclusions: In patients with asthma symptoms that are not well controlled with an ICS/LABA DPI, switching to an ICS/LABA pMDI provides an alternative choice that may improve asthma control. Highlights: This study evaluated acceptability and efficacy of switching asthma patients from an ICS/LABA DPI to an ICS/LABA pMDI. 83% of patients in the Switch cohort remained on ICS/LABA pMDI over 12 months of follow-up. At 3 and 12 months, the Switch cohort had significantly better FEV1 values than patients in the Maintenance cohort. At 12 months, the proportion of patients with controlled asthma increased in the Switch group.